Policy of Russia on the Caspian Sea - S. S. Zhiltsov (Проблемы постсоветского пространства, 2017)
The article considers the evolution of foreign policy of Russia in the Caspian Region at the present stage (1991-2014). It analyzes the changes in the Russian foreign policy approaches to the key problems of the region: international legal status of the Caspian Sea, extraction and transportation of the Caspian hydrocarbon resources, militarization and ecology.